Efecto morfológico y térmico de filmes flexibles de etilen vinil alcohol reforzados con óxido de grafeno - Yataco Lazaro y Cols., Lourdes Marcela (2018)
This work studied the morphological and thermal effects of ethylene vinyl alcohol (EVOH) film reinforced with 0.1 and 0.5 wt. % of graphene oxide (GO). The EVOH has been widely used in packaging for food to preserve the quality of the products due to its excellent gas barrier performance and its good transparency. The GO was prepared via chemical oxidation of graphite and was exfoliated into nanosheets using the sonochemical method.  The films were prepared by melt and blown extrusion, then were characterized by XRD, TG and SEM analysis, the correlation between properties was discussed.